Prospective direct comparison of antihypertensive effect and safety between high-dose amlodipine or indapamide in hypertensive patients uncontrolled by standard doses of angiotensin receptor blockers and amlodipine - Keisuke Okamura; Kazuyuki Shirai; Nao Totake; Tetsu Okuda; Hidenori Urata (Clinical and Experimental Hypertension, 2018)
Objective: When hypertension is uncontrolled by routine treatment with an angiotensin II receptor blocker (ARB) and the calcium channel blocker amlodipine (5 mg), the dose of amlodipine can be increased or a diuretic can be added. We investigated the more effective option in a prospective multicenter open-label study. Methods: Hypertensive patients were recruited if the target blood pressure (BP) in The Japanese Society of Hypertension 2009 guideline could not be achieved with standard-dose ARB therapy and amlodipine (5 mg). Patients: Patients were divided into three groups. Group-1 was switched to a combination of irbesartan (100 mg) and amlodipine (10 mg). Group‐2A was changed to a combination of irbesartan (100 mg), amlodipine (5 mg), and indapamide, while Group-2B received a standard-dose ARB and amlodipine (5 mg) plus indapamide. Patients were assigned by their attending physicians and were followed for 6 months. The primary endpoint was the antihypertensive effect of each regimen. Results: Group‐1 contained 85 patients, Group‐2A had 49 patients, and Group‐2B had 4 patients. We only analyzed Group‐1 and Group‐2A due to the small size of Group‐2B. In both groups, systolic BP and diastolic BP were significantly decreased up to 6 months (all p < 0.001). Reduction of systolic BP was greater in Group-1 than Group‐2A after 1 month and 6 months (both p < 0.05). Uric acid was increased in Group‐2A after 3 months, but not at 6 months. Conclusion: Although both regimens were effective for reducing BP, increasing amlodipine to 10 mg daily controlled hypertension without elevation of serum uric acid.